2018
DOI: 10.1039/c7cp05957d
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative ionisation of adamantane: a combined theoretical and experimental study

Abstract: aDiamond nanoparticles, or nanodiamonds, are intriguing carbon-based materials which, maybe surprisingly, are the most abundant constituent of presolar grains. While the spectroscopic properties of even quite large diamondoids have already been explored, little is known about their unimolecular fragmentation processes. In this paper we characterise the dissociative ionisation of adamantane (C 10 H 16 ) -the smallest member of the diamondoid family -utilising imaging Photoelectron Photoion Coincidence (iPEPICO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 39 publications
3
52
1
Order By: Relevance
“…IR induced dissociation of this fragment ion yields only a single product at m/z 77, presumably by H 2 loss. [46][47][48] The finding that the arenium ion is formed can also be compared with results for VUV induced dissociation reported recently by Candian et al [35] VUV dissociation was found to mostly result in a radical-cation C 6 H 8 * + fragment with the evenelectron C 6 H 7 + ion being a weaker contributor. Other isomers such as 1and 2-protonated fulvene (at + 39.3 and + 108.7 kJ/mol relative to protonated benzene, respectively) and the methyl-substituted cyclopentadienyl cation (+ 137.1 kJ/mol) do not match the recorded spectrum (see SI Figure S1).…”
Section: The M/z 79 Ionsupporting
confidence: 61%
See 4 more Smart Citations
“…IR induced dissociation of this fragment ion yields only a single product at m/z 77, presumably by H 2 loss. [46][47][48] The finding that the arenium ion is formed can also be compared with results for VUV induced dissociation reported recently by Candian et al [35] VUV dissociation was found to mostly result in a radical-cation C 6 H 8 * + fragment with the evenelectron C 6 H 7 + ion being a weaker contributor. Other isomers such as 1and 2-protonated fulvene (at + 39.3 and + 108.7 kJ/mol relative to protonated benzene, respectively) and the methyl-substituted cyclopentadienyl cation (+ 137.1 kJ/mol) do not match the recorded spectrum (see SI Figure S1).…”
Section: The M/z 79 Ionsupporting
confidence: 61%
“…Structures of the product ions from electron ionization of adamantane as suggested by mid-IR action spectroscopy (left) compared to the main ionic fragments found in VUV dissociative ionization as characterized by DFT potential energy surface computations. [35] Identification of the m/z 107 ion is perhaps most challenging in the present study; it is difficult to make a unique assignment based on the IR spectra, but two ethylbenzene and two meta-xylene structures are likely contributors to the ion population, while two protonated methylcycloheptatrienes isomers cannot be ruled out. [33] Furthermore, this finding is also in agreement with extensive C 10 H 16 * + PES computations that suggest that the formation of toluenium is kinetically favored.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations